“DYNAMIC GOVERNANCE” PADA BIDANG USAHA MILIK PESANTREN SALAFIYAH SYAFI’IYAH SUKOREJO SITUBONDO - Ach. Zubairi (Al-Idarah, 2020)
Dynamic Governance is the government's ability to formulate and implement policies in anticipation of rapid changes. The principles of Dynamic Governance are thinking ahead (the ability to identify environmental factors), thinking again (the ability to review various policies, strategies, and programs that are currently running) and thinking across (the ability to adopt thoughts, opinions and ideas outside the minset). As an institution that manages the economy, the BUMP pesantren continues to strive to become a dynamic institution, by trying to follow two major elements of the concept of dynamic governance, namely: dynamic capabilities and institutional cultures. Thinking ahead is the ability to analyze future developments. BUMP has carried out various business activities that keep up with the times by developing businesses that use information technology. Thinking again, BUMP always conducts business activities by visiting Islamic boarding schools which also have quite advanced business fields. Thinking across is BUMP's ability to learn from experiences or policies of other institutions and can adopt these policies to be implemented as needed.